THE EFFECT OF GENDER ON TAX LITERACY - Sri Hermuningsih; Pristin Prima Sari; Anisya Dewi Rahmawati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Abstract The research have duty to empirically examine the factors of gender differences in the understanding of tax study literacy. The method is a quantitative method using SPSS based on the results of Quiziz online. The analysis technique of samples used simple regression analysis and different test. The sample data uses management study program students. The results obtained are gender significant to the level of tax literacy. The Gender Men are better at tax literacy than women. The benefit is scientific development in the field of tax literacy and differences in understanding, especially taxes, between men and women, which is often called gender. Keywords: gender; literacy; taxes